Dimensión mítica y ritual en las representaciones literarias del narco - Jastrzębska, Adriana Sara (Romanica Silesiana)
Narco‑fiction, very popular in the recent Mexican and Colombian literature, emphasizes one of the determinants of narco‑culture: a deep rootedness in the primitive mentality and mythical thinking. Such roots translate into a particular religiosity, the cult of legendary narcos. The same mentality has driven the creation of a culture based on a ritual. The article analyzes examples of these phenomena, on the basis of selected texts of Colombian and Mexican narco‑fiction writers with the aim of showing that mythical thinking remains relevant in the postmodern and post‑political reality. Key words: narco, Colombian fiction, drug trafficking, narco‑culture, violence